2019
DOI: 10.2478/aoas-2018-0044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age at First Calving on First Lactation Milk Yield, Lifetime Milk Production And Longevity of Cows

Abstract: The objective of the study was to analyse the effect of age at first calving (AFC) on first lactation milk yield, lifetime milk production and longevity of dairy cows. The study used SYMLEK data on the milk yield and culling of 111 857 Polish Holstein-Friesian cows from the active population in Pomerania and Kujawy, Poland. The cows first calved during 2000–2009 and were used or removed from the herds until the end of 2015. For each cow, calculations were made of first lactation milk yield, lifetime milk produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
7
10
1
Order By: Relevance
“…This could be due to the fact that cows calved early had longer PL and more NL, LMP and LDMY compared to those calved late, in addition, there is a negative correlation between age at first calving and number of lactations and lifetime milk production. Similar results were found by Sawa et al, (2019) on Polish Holstein-Friesian and Sawa and Bogucki (2010) on Australian Holstein cows. Eastham et al, (2018) found that reducing age at first calving was associated with improving reproductive performance and increasing of number of lactations on Holstein and Holstein-Friesian cows in the UK.…”
Section: Number Of Lactations (Nl) Lifetime Milk Production (Lmp) Ansupporting
confidence: 84%
See 2 more Smart Citations
“…This could be due to the fact that cows calved early had longer PL and more NL, LMP and LDMY compared to those calved late, in addition, there is a negative correlation between age at first calving and number of lactations and lifetime milk production. Similar results were found by Sawa et al, (2019) on Polish Holstein-Friesian and Sawa and Bogucki (2010) on Australian Holstein cows. Eastham et al, (2018) found that reducing age at first calving was associated with improving reproductive performance and increasing of number of lactations on Holstein and Holstein-Friesian cows in the UK.…”
Section: Number Of Lactations (Nl) Lifetime Milk Production (Lmp) Ansupporting
confidence: 84%
“…This could be due to those cows calved early started productive life early, so they had longer PL compared to those calved late, in addition, there is a negative correlation between age at first calving and productive life. Sawa et al (2019) and Curran et al, (2013) arrived at the same conclusion on Holstein cows in Poland and USA, respectively. Sawa and Bogucki (2010) indicated cows had AFC ⩽22 months had the longest productive life.…”
Section: Productive Life (Pl)mentioning
confidence: 57%
See 1 more Smart Citation
“…This results, among others, from an association between the performance of primiparous cows and their lifetime production [ 20 , 21 ]. In this regard, the current attempts at searching for an association between certain production traits and culling reasons in cows are promising [ 22 , 23 ]. However, a qualitatively and quantitatively optimal selection of variables for prediction models and the use of sufficiently accurate analytical methods still remain a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing AFC can provide a lot of anumber of calving and milk production from cows during their lifespan and reduces high replacement costs. The typical AFC should be around 24 months (Sawa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%